Controlled Surface Assembly of Tobacco Mosaic Virus via Evaporation. - Leophairatana, Porakrit. (Tufts Archival Research Center, 2005)
In this thesis, I examined two routes in controlling the surface assembly of genetically modified tobacco mosaic virus (TMV) towards the creation of uniform and well-ordered 2-D arrays with high density and alignment. As a highly robust and well defined rod, TMV is an excellent candidate as a building block for surface assembly and fabrication of functional nanobio-devices. Dynamic self-assembly, via controlled solvent evaporation, was exploited as a facile route to assemble TMV onto the glass surfaces. In the first route, varying the concentrations of TMV and sodium phosphate led to control over TMV density, alignment, and percent coverage. In the second route, the temperature of the system was varied, leading to direct control over TMV array density and alignment. Atomic force microscopy (AFM) and contact angle measurements were employed for surface characterization. Via this fabrication method, I created well-ordered TMV arrays with very high density and nearly 100% surface coverage. I envision that my scheme to create well-controlled TMV array will open doors for the development of functional devices based on nanobio-materials.